China's new economic policy - Armin Bohnet; Günther Jaehne (Intereconomics, 1985)
China's new economic policy made headlines in December 1984 when a leading article in the People's Daily expressed the previously unthinkable opinion that the teachings of Marx and Engels could not be expected to solve all of China's present problems. What have been the main characteristics of the reform, which began five or six years ago, and how should its results so far be assessed? What are the prospects for the future?
Keywords: 330